Gender, sexuality and education: Educational policies scenario on the young and adolescents sexual and reproductive rights - Brabo, Tânia Suely Antonelli Marcelino [UNESP]; da Silva, Matheus Estevão Ferreira; Maciel, Talita Santana [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2020)
This article aims to reflect, through bibliographic review and documentary analysis, on the Brazilian educational policies scenario, regarding gender and sexuality categories, especially considering the young and adolescents sexual and reproductive rights. So, firstly the youth and adolescence constitution historical context is discussed, highlighting the need for Sexual Education to such audiences. The normative field design regarding the sexual and reproductive rights is presented below. Afterwards, the Sexual Education constitution and its insertion in the educational policies are discussed, including their initial and subsequent fundamentals. Finally, we seek to reflect on the gender and sexualities current insertion into Educational Policies, considering the achievements and needs that have been explained in the text.
Género, sexualidades y educación: Escenario de las políticas educativas sobre los derechos sexuales y reproductivos de jóvenes y adolescentes
Gênero, sexualidades e educação: Cenário das políticas educacionais sobre os direitos sexuais e reprodutivos de jovens e adolescentes
Keywords: Education; Gender and sexuality; Youth